A promising family literacy project based on male reading models - Isabelle Carignan; Robin L. Quick; Annie Roy-Charland; Marie-Christine Beaudry; Stéphanie Charbonneau (Brock University, 2021)
This article discusses an innovative family literacy project that was implemented in a community setting. Male trios consisting of a male relative, a struggling reader in elementary school and a pre-service teacher were created. The goal was 1) to develop student's motivation to read by using male reading role models and allowing the student to read what he truly enjoys in a non-school environment and 2) document male reading practices as trios. To document the progression of four male trios, we used a semi-directed interview, a focus group and a logbook. The results of this multiple-case research study showed an improvement regarding the student's motivation to read in the context of male trios, different reading practices inside the trios and a positive evolution in the relationship between the student and participating male relative has been observed.